2022
DOI: 10.1177/16878132221087510
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of cavitation characteristics for a high-speed inducer with a great flow rate

Abstract: Cavitation performance is a key parameter for a mine high-speed rescue pump, which reduces the stability and reliability of the entire unit. In this study, an experimental method was used to investigate the cavitation characteristics of an inducer installed on the impeller upstream. Hydraulic performance without cavitation was determined along with the cavitation performance, and a visualization experiment was implemented. The inducer head slightly decreased when the cavitation number started to decline; howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Xiang et al [12] developed a visualization test facility to study super-synchronous rotating cavitation and cavitation surge with varying tip clearance in the inducer. Zhang et al [13] observed that vortex cavitation was induced along with tip leakage vortex cavitation when the cavitation number decreased in the inducer. Wedge-shaped sheet cavitation then followed, which was subsequently succeeded by backflow vortex cavitation.…”
Section: Introductionmentioning
confidence: 99%
“…Xiang et al [12] developed a visualization test facility to study super-synchronous rotating cavitation and cavitation surge with varying tip clearance in the inducer. Zhang et al [13] observed that vortex cavitation was induced along with tip leakage vortex cavitation when the cavitation number decreased in the inducer. Wedge-shaped sheet cavitation then followed, which was subsequently succeeded by backflow vortex cavitation.…”
Section: Introductionmentioning
confidence: 99%
“…A typical evolution process of the cavitation was obtained, including the inception, the development, and the deterioration. Zhang et al [27] investigated cavitation behavior in a high-speed inducer with a great flow rate. When the cavitation number decreased, the vortex cavitation was induced along with the tip leakage vortex; subsequently, wedge-shaped sheet cavitation occurred, followed by backflow vortex cavitation.…”
Section: Introductionmentioning
confidence: 99%